DRUG UTILIZATION STUDY OF ANTIHYPERGLYCEMIC AGENTS IN OUTPATIENTS AT OPD CLINICS IN SOUTH INDIAN METROPOLITAN CITY - Khan, Kayamkani Abedulla (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To determine the drug utilization pattern of anti-diabetic medications in diabetic patients at diabetic outpatient clinics. Methods: A prospective observational study was conducted to find out the drugs utilization and prescriptions pattern of antihyperglycemic agents in diabetic outpatients in urban Telangana. This study was conducted for a period of six months, known cases of Diabetic Mellitus who were receiving antihyperglycemic medicines as outpatients of either sex of all age groups were included and Patients with gestational diabetes were excluded from the study. Results: In this study a total number of 250 prescriptions were collected which contained 1674 drugs. Among the prescriptions as an average each prescription contained more than 6.7drugs, this indicates polypharmacy. Among the antidiabetic drugs, metformin was found in a maximum number of prescription i.e. 109 (43.60%) and sitagliptin was found in a minimum number of prescriptions i.e.28 (11.20%) and most of the prescriptions contained antihypertensive agents, analgesics, vitamins and minerals preparations as supplements. Conclusion: This report alarm all the physicians and health care professionals about various drug interactions and adverse drug reactions which occur due to polypharmacy and also causing a more financial burden to chronic disease patients. Keywords: Drug utilization, Diabetes, Drug-drug interactions, Adverse drug reactions, DDD-defined daily dosage, ATC-Anatomical Therapeutic Chemical Classification and OPD-outpatient department